Peningkatan Kapasitas Kelompok Pengolah Dan Pemasar Hasil Perikanan (Poklahsari) “Bunga Anggrek” Kecamatan Ampenan Melalui Pelatihan Pengolahan Dan Pemasaran Ikan - Rosmilawati Rosmilawati; Asri Hidayati; Abdullah Usman; I G L Parta Tanaya (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2018)
Existence of Fishery Product Processing and Marketers Group of “Bunga Anggrek” in Banjar Hamlet of Banjar Village in Ampenan Sub district Mataram Municipality is very strategic where marine fishery products so far in Sub district of Ampenan have been marketed is only in local areas therefore group “Bunga Anggrek” can be a pioneers to local fisherman community to increase their capacity in processing and marketing fishery products. Main objective of this activity is making some kinds of fishery products with their good marketing strategy. Methods applied to accomplish the objectives are through training that is completed with good practices of making some kinds of fishery products and training of development of marketing strategy either for fresh fish or fishery products. The results showed that participants realized that processing fish into various processed products was very easy to do and could provide additional income for their families. In addition, their knowledge and insight in managing the business and in marketing the products of their business will also increase. This is possible because some of the material delivered by the team is enough to provide participants with knowledge that can increase their capacity in conducting a profitable business.